Energetics and biomechanics as determining factors of swimming performance: Updating the state of the art - Barbosa, T. M.; Bragada, J. A.; Reis, V. M.; Marinho, D. A.; Carvalho, C.; Silva, A. J. (Journal of Science and Medicine in Sport, 2010)
The biophysical determinants related to swimming performance are one of the most attractive topics within swimming science. The aim of this paper was to do an update of the "state of art" about the interplay between performance, energetic and biomechanics in competitive swimming. Throughout the manuscript some recent highlights are described: (i) the relationship between swimmer's segmental kinematics (segmental velocities, stroke length, stroke frequency, stroke index and coordination index) and his center of mass kinematics (swimming velocity and speed fluctuation); (ii) the relationships between energetic (energy expenditure and energy cost) and swimmer's kinematics; and (iii) the prediction of swimming performance derived from above mentioned parameters.